Implementasi Prinsip Good Governance dalam Peningkatan Kualitas Pelayanan Publik: Studi Kasus pada Pemerintah Daerah - Suwanda, I Gede Made; Tjenreng, Muhammad Baharudin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The implementation of good governance principles is crucial in efforts to enhance the quality of public services at the local government level. In this context, the principles of transparency, accountability, participation, and responsiveness serve as important foundations for creating better public services. This research aims to explore how the application of these principles can drive improvements in the quality of public services, as well as to identify the challenges faced in their implementation. Case studies drawn from several local governments in Indonesia provide a clear picture of good governance practices and their impact on public services. Through case studies in various regions, this research reveals how the application of these principles can increase public satisfaction with public services. Data obtained from surveys and field research will be analyzed to provide a clear overview of the relationship between good governance and the quality of public services.